(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In this paper we survey the ongoing advances in honeypot. A few striking recommendations and there investigation have been talked about. The parts of utilizing honeypot in training and in half and half condition with IDS have been clarified. In this paper we likewise characterize the utilization of mark system in honeypot for activity investigation. In the end we condenses every one of these viewpoints.